In Vitro Study Of The Efficacy Of Six Ethnoveterinary Plants Species Against Parasitic Nematodes And Caenorhabditis elegans In Nigeria - Gagman, Haladu Ali (2018)
Control of trichostrongylid nematodes using synthetic drugs have resulted to several complications such as increasing resistance of the nematodes to synthetic drugs, change in the quality of the products from the treated animals due to drugs residues in the tissues of the animals. These called for research to explore alternative to conventional drugs. The purpose of this work was to carry out in vitro study of the aqueous and methanol extracts Detarium microcarpum, Guiera senegalensis, Cassia siamea, Parkia biglobosa, Gmelina arborea and Boswellia dalzielii against trichostrongylid nematodes of small ruminants and the ivermectin resistant strain of Caenorhabditis elegans DA1316.